Makna Alif dalam Puisi Zikir D. Zawawi Imron dan Sajak Alif Ahmadun Yosi Herfanda - Rosalia, Sholeha; Wulandari, Yosi (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2020)
Alif means the first, saying the Supreme Life and is Sturdy and has the element of fire and Alif is formed from Ulfah (closeness) ta'lif (formation). With this letter Allah mementa'lif (unite) His creation with the foundation of monotheism and ma'rifah belief in appreciation of faith and monotheism. Therefore, Alif opens certain meanings and definitions of shapes and colors that are in other letters. Then be Alif as "Kiswah" (clothes) for different messages. That is a will. "IQRO" is a revelation that was first passed down to the Prophet Muhammad. Saw. Read it, which starts with the letter Alif and ends with the letter Alif. The creation of a poem is influenced by the environment and the self-reflection of a poet where according to the poet's origin, in comparing in particular Alif's poetry from the two poets. The object of this research is the poetry of Zikir by D. Zawawi Imron and Sajak Alif by Ahmadun Yosi Herfanda. This study uses a comparative method and sociology of literature. Through a comparative study of literature between the poetry of Zikir D. Zawawi Imron and Sajak Alif Ahmadun Yosi Herfanda, it is hoped that the public can know the meaning of Alif according to the poet's view. With this research, the Indonesian people can accept different views on the meaning of Alif in accordance with their respective understanding without having to look for what is right and wrong. The purpose in Alif is like a life, in the form of letters like a body, a tree that is cut to the root, from the heart is split to the seeds, then from the seeds are split so that nothing is the essence of life. So, it is clear that Alif is the most important and Supreme letter. Talking about the meaning of Alif as the first letter revealed on earth. After the letter Alif was revealed, 28 other Hijaiyah letters were born. The letter Alif is made the beginning of His book and the opening letter. Other letters are from Alif and appear on him.